Morphological and soil measurements for determining ecotypic variation in Trifolium tembense germplasm in the Ethiopian highlands - Akundabweni, L.S.; Lazier, John R.; Lemme, G. (1991)
A study was initiated on selected populations of Trifolium tembense collected from the Ethiopian highlands. The species was an annual autogamous clover which is native to the African highlands. In the study, both plant and soil variables were utilized for investigating possible LbP (local breeding populations) variation in the species.